Pengaruh Interval Waktu Data Curah Hujan dalam Analisis Intensitas Durasi Frekuensi di Provinsi Lampung - Mardiyansyah Mardiyansyah; Ahmad Zakaria; Dyah Indriana Kusumaastuti (UNIVERSITAS LAMPUNG, 2019)
in a reservoir or river, it is necessary to know the size of the flood discharge plan used as a basis for calculating the size of the canals and their complementary buildings. Troubleshooting using Hydrological analysis, Intensity Duration Frequency (IDF) requires frequency analysis using a series of data obtained from rain data records. The scope of this research covers the area of Lampung Province, namely BMG Radin Inten II station and BMG Maritim Panjang station. From the comparison of the IDF curve analysis between rainfall data for short time intervals and daily rainfall data, the percentage difference between rainfall intensity differences in each duration and at certain return periods is obtained. IDF Curve Analysis for Daily Rain Data uses the Mononobe method, from the results of IDF curve analysis between rainfall data for short time intervals with daily rainfall data at BMG Radin Inten II station there is a difference in the ratio of high intensity up to 3 times or > 300%, whereas in BMG Maritim Panjang station only the difference in ratio > 100%.